Efek Risiko Bisnis, Risiko Keuangan Dan Growth Opportunity Pada Struktur Modal Perusahaan Manufaktur Food And Beverage - Makarima, Naeli; Cahya, Bayu Tri; Affandi, Johan ; Arifah, Tri Hanum; Hanifah, Umi (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research is research that aims to analyze the influence of business risk, financial risk, and growth opportunity on the capital structure of food and beverage manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2020-2022 period. The background to this research is the occurrence of fluctuations which tend to decrease the company's capital structure. This type of research is associative research. The kind of approach used is a quantitative approach. Sampling in this research used the purposive sampling method. Purposive sampling is a technique for determining samples based on special considerations so that they are worthy of being used as samples. The sample in this study consisted of 14 food and beverage manufacturing companies listed on the Indonesian Sharia Stock Index. The data used in the research is secondary data obtained from the official website of each relevant company. The research results show that partial financial risk has a positive effect on capital structure. Meanwhile, business risk and growth opportunity do not affect capital structure.